DIAGNOSTIC RESULTS AND TREATMENT OF INTERNAL TMJ DISORDERS UNDER CONTROL OF MAGNETIC RESONANCE IMAGING - V. Shybinskyi (Ukrainian Medical Stomatological Academy, 2016)
MRI is a supporting method not only for the recognition of internal disorders, but also for establishing the therapeutic position of the lower jaw, which is very important and having no definition of such position, as it is one of the major causes of unsuccessful patients' treatment with articular disc displacement. Improperly installed medical position makes the reposition of the articular disc impossible. The aim of the research is to estimate the possibilities of magnetic resonance imaging (MRI) in the diagnosis of TMJ disorders and internal evaluation of their treatment. The optimal protocol of MRI of TMJ examination has been processed and explored to detect magnetic resonance images of internal disorders in the TMJ, which gave the most accurate information sufficient to choose an adequate treatment plan and evaluate the results with the use of special primary coil for magnetic resonance imager SIGNA CONTOUR by firm GE magnetic field of 0.5 T. Using the same method 21 patient with various internal TMJ disorders is treated. The overview was performed in oblique sagittal planes perpendicular to the head TMJ with opened and unopened mouth, and in the frontal plane, holding the lower jaw in the set position by special clamps, previously made in the clinic. Clamps' application of certain position of the mandible, such plan is to study using MR imaging is obligatory, as the articular disc changes its position simultaneously with the change of the mandible head. The research performed in a random position of the mandible, have limited diagnostic value. Analysis of the clinical examination and diagnostic overview of patients allows to state that in average 4-6 months after initiation of treatment and diagnostic usage, patients noticed the absence of complaints in the part of the TMJ. Thus, according to MR-tomography researches joints, joint discs inherent held position that the evidence of normalization of relations elements of the TMJ. It was the basis for the final stage of orthopaedic treatment - prosthetic dentures for permanent wearing. Magnetic resonance imaging is a highly informative non-invasive method of diagnosis that allows you to visualize bone and soft tissue TMJ structural elements, to determine the presence of structural changes occurs in a cell-capsular ligaments in various forms of TMJ internal disorders. The criteria for evaluation of such disorders is mutual accommodation of soft elements, their form and anatomical integrity of the open and closed mouth of the patient relative to the bone of structures defined by the MR-tomograms as the bias sagittal and frontal projections. The use of MR imaging allows not only recognize and differentiate internal TMJ disorder, which is very important while choosing a treatment, and is a complementary treatment for establishing the position of the mandible. Inappropriate position defined therapeutic mandibular occlusal tire to reposition prevents TMJ articular disc, which is one of the major causes of failure while performing treatment of patients with displacement of the articular disc.